From bench to bedside: therapeutic potential of natural antioxidants in diabetic neuropathy - Zhang, Yanxian; Yao, Lili; Lyu, Yongmei; Tang, Zhuqi; Liu, Xiaoyu; Duan, Xuchu (Frontiers in Cell and Developmental Biology, 2025)
Diabetic neuropathy (DN) is a prevalent and debilitating complication of diabetes, causing substantial morbidity and negatively impacting the quality of life for millions of individuals worldwide. The pathogenesis of DN is complex, with oxidative stress (OS) emerging as a key factor contributing to nerve damage through mechanisms like lipid peroxidation, protein modification, and DNA damage. This review examines the role of natural antioxidants in alleviating symptoms of DN, summarizes recent progress in fundamental and clinical research on antioxidants in treating DN. It emphasizes the mechanisms by which compounds such as polyphenols, terpenoids, and carotenoids counteract OS, a critical factor in the pathogenesis of DN. These antioxidants, derived from various natural sources, show promise in enhancing nerve conduction velocity, reducing neuropathic pain, and improving glucose metabolism. Clinical trials, particularly those involving alpha-lipoic acid, provide evidence supporting the benefits of antioxidant therapy in enhancing nerve function. The review highlights the necessity for further research into natural antioxidants to develop more effective treatment strategies for DN.